2017
DOI: 10.1007/s00592-017-0971-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinal neurodegeneration in patients with type 1 diabetes mellitus: the role of glycemic variability

Abstract: AimsRecent studies have identified neuroretinal abnormalities in persons affected by diabetes mellitus, before the onset of microvascular alterations. However, the role of glycemic variability (GV) on early retinal neurodegeneration is still not clarified.MethodsTo explore the relationship between glycemic control and neuroretinal characteristics, 37 persons with Type 1 diabetes mellitus (Type 1 DM) divided into two groups with no signs (noRD) and with mild non-proliferative diabetic retinopathy (NPDR) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 48 publications
0
52
1
Order By: Relevance
“…Perrot et al found that glucose fluctuation would increase pulsatile ocular blood flow, which may cause damage to the endothelium of the choroidal vessels and resulting in retinal hypoxia in patients with type 2 diabetes. Picconi et al also showed that early structural damage of neuroretina was related to glucose fluctuation in type 1 diabetes. These prior studies are consistent with the present study showing that higher fasting glucose variability was correlated with the development and progression of DR.…”
Section: Discussionmentioning
confidence: 97%
“…Perrot et al found that glucose fluctuation would increase pulsatile ocular blood flow, which may cause damage to the endothelium of the choroidal vessels and resulting in retinal hypoxia in patients with type 2 diabetes. Picconi et al also showed that early structural damage of neuroretina was related to glucose fluctuation in type 1 diabetes. These prior studies are consistent with the present study showing that higher fasting glucose variability was correlated with the development and progression of DR.…”
Section: Discussionmentioning
confidence: 97%
“…Increased triglyceride levels were reported to be associated with increased INL thickness in type 1 DM subjects with early retinal degeneration. 41 Moreover, fenofibrate (FA) therapy was shown to lower the progression of DRP by reducing triglyceride levels in type 2 DM subjects. 42,43 However, the protective effect of FA was reported to be independent of its lipid-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…GV has been associated with a number of markers of vascular complications, independent of average glucose control. For example, GV has been associated with retinal thickening and neurodegenerative defects in the retina that were independent of HbA1c . It has also been associated with markers of autonomic cardiovascular (CV) function such as heart rate variability, particularly during the night .…”
Section: Glycaemic Variability and Microvascular Outcomesmentioning
confidence: 99%
“…For example, GV has been associated with retinal thickening and neurodegenerative defects in the retina that were independent of HbA1c. 27,28 It has also been associated with markers of autonomic cardiovascular (CV) function such as heart rate variability, particularly during the night. 29,30 More recently, CGMdefined GV has been associated with the presence of CV autonomic neuropathy.…”
Section: Glycaemic Variability and Microvascular Outcomesmentioning
confidence: 99%